2011
DOI: 10.1063/1.3528124
|View full text |Cite
|
Sign up to set email alerts
|

Major deep levels with the same microstructures observed in n-type 4H–SiC and 6H–SiC

Abstract: Temperature dependent recombination dynamics in InP/ZnS colloidal nanocrystals Appl. Phys. Lett. 101, 091910 (2012) Intrinsic defect in BiNbO4: A density functional theory study J. Appl. Phys. 112, 043706 (2012) The CuInSe2-CuIn3Se5 defect compound interface: Electronic structure and band alignment Appl. Phys. Lett. 101, 062108 (2012) Investigation of deep-level defects in conductive polymer on n-type 4H-and 6H-silicon carbide substrates using I-V and deep level transient spectroscopy techniquesMajor dee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
36
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 37 publications
1
36
0
2
Order By: Relevance
“…One sample was further annealed in a sublimation reactor at 1600 C. Only slightly reduced signatures of Z 1=2 or EH6/7 are left in the DLTS spectrum as previously reported by several authors. 16,21,22 The annealing of these two centers takes place at rather high temperatures, T % 2000 C. The annealing of the EB-centers occurs at higher temperatures than for the M-center and the EH1/EH3, which were proposed to be due to the recombination of mobile carbon interstitials but at lower temperatures than the Z 1=2 or EH6/7, which were attributed to the carbon vacancy. The EB-centers are thus likely carbon interstitial related complex defect.…”
Section: Annealing Of Eb-centersmentioning
confidence: 99%
See 1 more Smart Citation
“…One sample was further annealed in a sublimation reactor at 1600 C. Only slightly reduced signatures of Z 1=2 or EH6/7 are left in the DLTS spectrum as previously reported by several authors. 16,21,22 The annealing of these two centers takes place at rather high temperatures, T % 2000 C. The annealing of the EB-centers occurs at higher temperatures than for the M-center and the EH1/EH3, which were proposed to be due to the recombination of mobile carbon interstitials but at lower temperatures than the Z 1=2 or EH6/7, which were attributed to the carbon vacancy. The EB-centers are thus likely carbon interstitial related complex defect.…”
Section: Annealing Of Eb-centersmentioning
confidence: 99%
“…12 Several studies in different temperature ranges and for different irradiation energies were previously presented. Multistage annealing processes are calculated for Frenkel pairs in irradiated SiC 20 and measured in electron irradiated n-type 4H-SiC; 16 highly movable related defects anneal first before elementary, stable defects start to decrease, e.g., Z 1=2 and EH6/7 above 1700 C. 12,16,21,22 The annealing can be enhanced under injection of carriers due to electron-hole recombination at the defect site, 23 which may change the charge state. 24 The defect migration is thus increased.…”
mentioning
confidence: 99%
“…The shape of the two peaks is very similar for all polytypes. Sasaki et al 4 recently showed that these levels most probably originate from the same defect, likely the carbon vacancy. They additionally concluded that the LangerHeinrich rule, which was previously only applied for transition metals, is valid also for intrinsic defects in SiC.…”
mentioning
confidence: 99%
“…Most investigations were conducted on the 4H-SiC polytype and only recently, a comparative study on defects in 4H-SiC and 6H-SiC and their behavior after oxidation has revealed common characteristics on the origin of these intrinsic defects. 4 Previously, defect studies on 3C-SiC bulk material 5 and cubic layers grown on Si have been done. [6][7][8][9] However, due to the heteroepitaxial growth, it has not been clear, which of the defects are related to the interface and which that are related to 3C-SiC.…”
mentioning
confidence: 99%
“…It is known, that the valence bands of the different SiC-polytypes [31] align and previously it was observed, that also intrinsic defects align [29,32]. Hemmingsson et al [16] detected a multistable defect present in 6H-SiC.…”
Section: Comparison With Metastable Defect Detected In 6h-sicmentioning
confidence: 99%